2004
DOI: 10.4321/s0213-12852004000600004
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de boca ardiente: Eficacia de la aplicación tópica de capsaicina. Estudio piloto

Abstract: El síndrome de boca ardiente es un cuadro clínico complejo en el que el paciente manifiesta una sensación de escozor o ardor intrabucal sin que aparezcan lesiones clínicas objetivables. Objetivo: Valorar la eficacia mediante la aplicación de un gel de capsaicina a una concentración de 0.025 mg., en pacientes con síndrome de boca ardiente. Pacientes y método: Se estudiaron a un grupo de 29 pacientes a los que se les realiza un protocolo de recogida de datos que incluye anamnesis, historia médica, exploración bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 12 publications
6
15
0
1
Order By: Relevance
“…Such a result is in agreement with the reviewed literature on BMS, and with the involvement of other structures to a lower degree (2)(3)(4)6) . The xerostomia group mentioned a larger amount of structures affected with dry mouth, including the lips and the oropharynx (16,21,22) .…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Such a result is in agreement with the reviewed literature on BMS, and with the involvement of other structures to a lower degree (2)(3)(4)6) . The xerostomia group mentioned a larger amount of structures affected with dry mouth, including the lips and the oropharynx (16,21,22) .…”
Section: Discussionsupporting
confidence: 81%
“…This datum may point that both BMS and dry mouth seem to affect mainly the population aged 50 years or around (1,15,24) . Regarding patients' clinical history, the symptomatic groups showed similarities in may aspects, which agrees with the reviewed literature (2,(4)(5)(6)(7)(8)11,16,22,23) . Some studies, however, found variations especially regarding the intensity of the symptom (4,22,24) .…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations